The Refuge of Letters. Rosa Chacel, Máximo José Kahn and the Jewish Question (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
With the arrival of the first news about the “final solution” of Nazi Germany, Republican exiles of Jewish origin present in Spanish-speaking America began to debate the issue and, above all, to question their role as intellectuals and to reflect on their own identity. Our purpose is to offer a new approach to the reception of the Shoah in the Republican intellectual community and, within this “group”, to the participation of exiles of Jewish descent in the debate on what actions to take to welcome European Jewish refugees and how to talk about the Holocaust. To do this, we will investigate the relationship between two exponents of literary intelligence in exile, Rosa Chacel and Máximo José Kahn, and the role that both played in the face of the Holocaust, starting from their friendship, which went back to before the war and continued in the diaspora; after presenting a brief historical-literary overview of the Spanish “Jewish question”, we will focus on the study of the correspondence between Chacel and Kahn and their literary production related to the topic.
Keywords: Rosa Chacel; Máximo José Kahn; Shoah; Spanish Republican Exile; Literature and Commitment